Arcobaleni e nuvole cronaca di una pandemia - Venuta, Fabrizia (Fuori collana, 2023)
The Covid-19 pandemic changed our lives forever. Our certainties have been questioned by having found ourselves living through something more similar to a film than reality, something that none of us could ever have imagined would happen. Our kids went through this period, which has not ended yet, with their customary joy, but also with the sadness of those who feel they have missed moments that will never return. They have expressed all this in diary pages that have been collected and published in this book and in some of them is quoted a phrase that had gone viral on the Internet: "Remember that our grandparents were ordered to go to war, while they are asking us to stay on the couch".